2004
DOI: 10.1038/sj.bjc.6601568
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics in mice and growth-inhibitory properties of the putative cancer chemopreventive agent resveratrol and the synthetic analogue trans 3,4,5,4′-tetramethoxystilbene

Abstract: Resveratrol (trans-3,5,4 0 -trihydroxystilbene) is a naturally occurring polyphenol with cancer chemopreventive properties in preclinical models of carcinogenesis, including those of colorectal cancer. Recently, a variety of analogues of resveratrol have been synthesised and investigated in in vitro assays. One analogue, 3,4,5,4 0 -tetramethoxystilbene (DMU 212), showed preferential growth-inhibitory and proapoptotic properties in transformed cells, when compared with their untransformed counterparts. As part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
170
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(192 citation statements)
references
References 38 publications
(38 reference statements)
13
170
1
Order By: Relevance
“…[22] Such is the case of DMU-212 [(E)-3,4,4Ј,5-tetramethoxystilbene], which has recently disclosed a strong anticancer activity with higher chemoprotective activity than that of resveratrol. [23] As part of our continuous interest in the preparation and 76 application of active metals, [24] we reported the fast synthesis of nickel(0) nanoparticles (NiNPs), from different nickel(II) chloride-containing systems in THF, by using lithium powder and a catalytic amount of an arene, as reducing…”
mentioning
confidence: 99%
“…[22] Such is the case of DMU-212 [(E)-3,4,4Ј,5-tetramethoxystilbene], which has recently disclosed a strong anticancer activity with higher chemoprotective activity than that of resveratrol. [23] As part of our continuous interest in the preparation and 76 application of active metals, [24] we reported the fast synthesis of nickel(0) nanoparticles (NiNPs), from different nickel(II) chloride-containing systems in THF, by using lithium powder and a catalytic amount of an arene, as reducing…”
mentioning
confidence: 99%
“…The results of the tests conducted by Sale et al [37] point out an increased DMU-212 bioavailability in the small intestine, colonic mucosa and brain as compared to RSV. Higher DMU 212 availability in brain suggests that it overcomes the blood-brain barrier more easily than RSV.…”
Section: Dmu-212mentioning
confidence: 99%
“…DMU-212, however, undergoes oxidation in liver, primarily O-demethylation at positions 3,4 or 4 ' and hydroxylation. Sale et al [37] have demonstrated that methylation of hydroxyl groups with RSV and the introduction of new methyl group in position 4 destroys the ability to inhibit COX-2 expression. However, it does not limit the potential for inhibiting the adenomas formation and the ability to reduce PGE-2 level.…”
Section: Dmu-212mentioning
confidence: 99%
See 1 more Smart Citation
“…In view of resveratrol's anti-tumor potential, it is reasonable to design new chemotherapeutic agents using resveratrol as a prototype. It has been reported that a resveratrol derivative, 3,4,5,4'-tetramethoxystilbene, has stronger anti-proliferative properties in human colon cancer cells [9] . Therefore, we synthesized a series of methoxy groupmodified stilbenes and tested their cytotoxicity in human lung On the other hand, the addition of a halogen group during the structural modification of resveratrol has seldom been reported.…”
Section: Introductionmentioning
confidence: 99%